2016
DOI: 10.17219/acem/36417
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Maintenance Infliximab Therapy for the Treatment of Crohn’s Disease with Perianal Fistulas in Children: Retrospective, Multicenter Study

Abstract: Background. Infliximab is a biological drug used for the treatment of Crohn's disease in children. Objectives. The aim of this retrospective study was the estimation of effectiveness and safety of infliximab in the treatment of Crohn's disease with perianal fistulas in children. Material and Methods. Analysis comprised 50 children with Crohn's disease with perianal fistulas aged 9 to 18 years (16 girls and 34 boys) who failed to respond to conventional therapy. The children were divided into two groups: the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…32,33 In a retrospective multicenter study on 50 patients with pediatric perianal Crohn's disease, infliximab was effective and safe as 72% of patients had a complete closure of fistulas, while 30% had a fistula recurrence during the first year after treatment. 4 In children, anti-TNF-α is recommended to be continued for at least 1 year following abscess drainage. 5 The combination of infliximab and seton placement in the treatment of perianal fistulas has been shown to result in better primary treatment results, longer effect duration and lower recurrence rate compared with either treatment alone.…”
Section: Medical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 In a retrospective multicenter study on 50 patients with pediatric perianal Crohn's disease, infliximab was effective and safe as 72% of patients had a complete closure of fistulas, while 30% had a fistula recurrence during the first year after treatment. 4 In children, anti-TNF-α is recommended to be continued for at least 1 year following abscess drainage. 5 The combination of infliximab and seton placement in the treatment of perianal fistulas has been shown to result in better primary treatment results, longer effect duration and lower recurrence rate compared with either treatment alone.…”
Section: Medical Managementmentioning
confidence: 99%
“…2,3 The main management goals for the perianal Crohn's disease are long-term remission and prevention of complications (such as recurrent perianal sepsis, chronic fistula formation, strictures, and fecal incontinence), limitation of adverse effect on growth and development, hospital admissions, and the need for surgical procedures, as well as improvement of quality of life. 4,5 These goals are best achieved by multidisciplinary approach with combined pharmacological and surgical measures depending on the inflammatory activity, abscess formation, location, and clinical course of the perianal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 166 were included in the full text review. Seventy‐six were further excluded, leaving 90 studies for data extraction [17–106] (Figure 1). Of the 90 studies, there were 53 retrospective studies, 16 prospective observational studies, 16 RCTs, four case series and one cross‐sectional study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, early introduction of IFX was effective for maintenance of longterm remission in 14 out of 15 patients [17]. A retrospective observational study at another institution [18] that examined the efficacy of IFX for patients with CD with anal fistula stated that the anal fistula was closed in 70% of patients and highlighted the efficacy of IFX in such patients. Similarly, in our study, closure of the anal fistula was confirmed in all 7 patients using IFX, and there was no recurrence.…”
Section: Discussionmentioning
confidence: 99%